Nazi Games : The Olympics of 1936 - Large, David Clay (New York Norton, 2007)
Athletics and politics collide in a critical event for Nazi Germany and the contemporary world. The Olympic festival was a crucial part of the Nazi regime's mobilization of power. The torch relay--that staple of Olympic pageantry--first opened the summer games in 1936 in Berlin. Proposed by the Nazi Propaganda Ministry, the relay was to carry the symbolism of a new Germany across its route through southeastern and central Europe. Soon after, the Wehrmacht would march in jackboots over the same terrain. This book offers a blend of history and sport: it includes an account of the international effort to boycott the games, derailed by the American Olympic Committee. It also recounts the dazzling athletic feats of these Olympics, including Jesse Owens's four gold-medal performances, and the marathon victory of Korean runner Kitei Son, with the Rising Sun of imperial Japan on his bib.--From publisher description.
Include Illustrations, Notes and Index
Keywords: National socialism and sports -- Olympic Games